Microstructure evolution in flow formed IN 718 products and subsequent fatigue crack growth properties - Martin Bache (Fatigue & Fracture of Engineering Materials & Structures, 2018)
With the drive towards cost‐effective routes for the manufacture of engineering components, flow forming technologies are now under consideration for the production of structural axisymmetric geometries such as tubes and cones. This near net shape process is known to offer improvements in material utilisation when compared with traditional processes where substantial final machining is required. The microstructure, evolved as a result of the flow forming process together with subsequent heat treatments, will govern associated mechanical properties. Laboratory measurements of the structure‐property relationships of flow formed material can be problematic, mainly because of the restrictions imposed on the extraction of conventional specimen geometries since most of the finished tubular or cone structures will contain thin and curved walls. The development of a suitable specimen design and associated test technique for the measurement of fatigue crack growth rates at room and elevated temperatures is presented. Data obtained from flow formed Inconel 718 (IN 718) will be compared with specimens of the exact same geometry but machined from conventionally forged IN 718 stock. This allowed for validation of the novel flow formed test in addition to an assessment of the damage tolerance of the flow formed variant. The intimate relationship between local microstructure and fracture mechanisms will be described.